Myocardial hypertrophy and intracardial hemodynamics in children with bicuspid aortic valve - А. V. Kamenshchyk; O. G. Ivanko (Zaporozhye State Medical University, 2017)
Bicuspid aortic valve is one of the most common congenital heart diseases with low manifestation in childhood and severe consequences in adults that determines the importance in early diagnostics of myocardial changes in this anomaly. According to the literature the polymorphisms in the genes of NFATC family could result both in impaired embriogenetic valves formation and development of postnatal myocardial hypertrophy. The aim of the study was to detect the early changes of intracardial hemodynamics at aortic valve in children with bicuspid aortic valve (BAV) and establish their interrelations to the signs of myocardial hypertrophy in these children. Materials and methods: Dopplerograhphic study of basic intracardiac hemodynamics parameters in 38 children with BAV and in 28 children of control group was conducted. The results were processed statistically by Student's t-test, correlation analysis and multiple regression. Results: In the result of study the moderate concentric left ventricle myocardial hypertrophy development was detected in 62 % of children with BAV which is accompanying to significant increasing of blood flow velocity and pressure gradient at aortic valve. There were not established significant correlations between the parameters of hemodynamics at valve and left ventricle's posterior wall depth and septum depth whereas the highest inputs of these values were obtained in the left ventricle systolic dimension and volume and less in the hypertrophic signs. Conclusions: In children with BAV the moderate concentric myocardial hypertrophy with significant changes of intracardial hemodynamics at aortic valve takes place with the highest inputs in left ventricle volumetric values The obtained data serves as a substantiation for the treatment and prevention of it further development. bicuspid aortic valve; children; heart hypertrophy; dopplerechocardiography; hemodynamics; regression analysis